Analysis of turbine pressure, feed water temperature and condenser back pressure on performance of power generation system for lead-based reactor - Muhammad Salman Khan; Yong Song; Chi Xu (Case Studies in Thermal Engineering, 2022)
Lead-based reactors have high core outlet temperature and have the potential to achieve high performance of Power Generation System (PGS). The increase in the thermal performance of the PGS is really a key challenge for the lead-based reactor. In this paper, a reference scheme with two reheater has been chosen for lead-based reactor with 400 MWth to improve the thermal performance of the system based on the optimization of inlet parameters to overcome and meet the energy demands. The influence of turbine pressure, feed water temperature and condenser back pressure have been analyzed to improve the performance of lead-based power reactor. The analysis results show that as turbine pressure is increased from 18 MPa to 22 MPa at steam inlet temperature of 465 °C, the thermal efficiency of system is increased from 44.30% to 46.35%. As PGS is operated at 22 MPa and the temperature of the feed water is increased from 335 °C to 356 °C, the thermal efficiency of system can be increased up to 49.45% and it decreased with the increase of condenser back pressure from 0.004 MPa to 0.015 MPa. The maximum thermal efficiency of the system was 45.28% at 0.004 MPa condenser back pressure. This work can be used for the analysis and optimization of a nuclear power plant based on the heavy metal cooled reactor concept.